Sistem Informasi Kepegawaian Cuti Karyawan Berbasis Website Pada AUTO2000 di Denpasar - Wisnawa, Komang Surya; sugiartawan, putu (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2020)
Furlough is one of the employee rights and obligations are given by the company that each employee has the right to leave at the place where their respective company works. Furlough can be used for employees not working for certain reasons such as personal needs, illness, or for other purposes. 13 of 2003 regarding employment. Currently, there are still many companies whose leave handling is still manual. Employees often do not know the rest of the furlough, the application for leave also still uses a form or card that must be filled out and then submitted to the authorized department. The design of this website, as for several stages including interviews, data collection, observation of data analysis then continued with the design of the employee furlough staffing website by analyzing and designing each component using UML with a presentation using use case diagrams, activity diagrams, sequence diagrams, and class diagrams. With the existence of a leave application personnel information system which is a means of information media that can easily find out all information related to leave application and leave rights owned by each employee.